Monitoring Daya Menggunakan Algoritma Shortest Job First Pada Wireless Sensor Network - Tadya Adi Prana; Mochammad Hannats Hanafi Ichsan; Gembong Edhi Setyawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wireless sensor network (wireless sensor networks) is a wireless network that consists of a collection of sensor nodes spread over a certain area (sensor field). Each sensor node has the capability to collect data and communicate with other sensor node. From a number of problems in its implementation, the main issue is that of the WSN energy consumption. It is in result by the power supply on the node only supplied by a battery to its operations, thus having a limited energy reserves. Solution problem the authors implement Algorithms SJF (Shortest Job First) where the Algorithm placed on nodes that have the shortest path, the function of the RF315/433Mhz where the module will help data delivery Wireless. For the monitoring mechanism of the power available on each node mikrokontroller ATmega32, sensors, Sensor Voltage ACS712, DHT11 Sensor, as well as provided with the RTC module as the data source time function as a time stamp over the system. Implementation of high accuracy Algorithm SJF has in testing data transmission is done at 5 times the delivery with a certain distance, in a closed space optimal distance results obtained its data delivery is +100 cm with an average time transmission of 1s, and at a distance of +120 cm or more could still be done sending data but the data delivery success percentage is only 80%.